Pengembangan Media Pembelajaran Pop Up Book Berorientasi Kearifan Lokal Hari Raya Karo Suku Tengger Bromo Kelas III di SDN Ngadisari I Kabupaten Probolinggo - Susanti, Olik; Wardana, Ludfi Arya; Kasdriyanto, Didit Yulian (CV. ITTC INDONESIA, 2024)
Learning media such as Pop Up Books based on local wisdom in thematic learning can be an important tool for teachers to overcome students' lack of enthusiasm and responsiveness to learning materials at school. Pop Up Books are not only valid and easy to use, but also practical as teaching materials for elementary school students. Its advantage lies in its attractiveness through 3D images that match the material, creating an interesting learning experience. In addition, the connection with local wisdom allows students to share knowledge about their local traditions, increasing interaction and exchange of information between them. Research also enables the development of innovative ideas that can be applied in educational contexts. One type of research that can be carried out is R&D research and development using the Borg & Gall development model which is narrowed down into 7 steps according to research needs. The results of the small group trial assessment showed that the media developed received a positive response (yes) of 96.6% and a negative response (no) of 6.6%. Evaluation of large group trials, the media that has been developed received a positive response of 98%, while a negative response was 8%. The results of the trials that have been carried out state that the Pop Up Book media is suitable for use in grade III elementary schools based on local wisdom that upholds the values ​​contained therein. The development of Pop Up Book Learning Media can be concluded that the media has received a good response from validators and respondents. The assessment from media experts showed a media value of 45, with a percentage reaching 80%, without any revisions, from material experts the media value was 58, with a percentage reaching 96.6% after undergoing revisions, practicality experts with a revised practicality value of 41 with a percentage 74.54%. A small group trial of 3 students on the media that had been developed received a positive response of 98%, while a negative response was 8%. A large group trial of 10 students of the media that had been developed received a positive response of 98%, while a negative response of 8% was appropriate. to use.